The Role of Fibroblast Growth Factor Receptors Inhibitors in Bladder Cancer - Ho Kyung Seo; Eui Hyun Jung; Sora Yang; Hye Won Lee (Journal of Urologic Oncology)
Dysregulation of fibroblast growth factor (FGF)-receptor (FGFR) signaling, which is implicated in various oncogenic processes, including tumor proliferation, survival, migration, invasion, and angiogenesis, has been identified as a critical factor in urothelial bladder cancer (UBC) progression. This has led to the development of novel FGFR-targeted therapies. Erdafitinib is an oral selective pan-FGFR tyrosine kinase inhibitor approved for locally advanced or metastatic urothelial cancer in patients with FGFR3 alterations who progress on both platinum-based chemotherapy and immunotherapy. The approval of FGFR inhibitors (FGFRis), such as erdafitinib, and ongoing research into combination therapies with immune checkpoint inhibitors (ICIs) signify a promising shift in the treatment paradigm for advanced/metastatic UBC despite challenges such as the variable efficacy of FGFRis and treatment-related toxicity. In this study, we review the FGFR signaling pathway and the impact of altered FGFR signaling on UBC tumorigenesis, the clinical development of FGFRis, the rationale for FGFRi-ICI combinations, and future directions.